THE SIGNIFICANCE AND CHALLENGES OF LEGAL REGULATION OF CROSS-BORDER FLOW OF PERSONAL INFORMATION FROM THE PERSPECTIVE OF NATIONAL SECURITY (Innovate Conferences, 2025)
As the wave of digitalization sweeps the world, the cross-border flow of personal information has become an important link supporting global economic activities. However, the national security risks associated with this process are increasingly valued by countries. How to effectively maintain national security while promoting the free flow of data has become a core issue in legislation and policy making in the current international community. This article explores the significance of legal regulation of cross-border flow of personal information and the practical challenges it faces from multiple dimensions, including data sovereignty, geopolitical game, systemic risk prevention, international rules game, and balance between security and development, and proposes strategies and suggestions for defending data sovereignty in the future.